In Search of Entrepreneurial Learning: Towards a Relational Perspective on Incubating Practices - Christine Thalsgård Henriques (Copenhagen Business School (CBS), 2016)
The world wants more entrepreneurs so badly, that it has become a major priority of governments all over the world trying to produce them. Based on Industrial PhD collaboration between the Danish Science Park, Symbion A/S and Copenhagen Business School, this dissertation presents a unique opportunity to study how the interactions between technology-based entrepreneurs and an Accelerator programme may lead to increased entrepreneurial capacity, learning and growth. The Industrial PhD setting offers privileged access to entrepreneurs, advisors, incubator management and investors, and we get to listen to stories seldom told in this field. As follows, the write-up of the ethnographic fieldwork is a narrative multi-voiced analysis in search of entrepreneurial learning in an incubator context. The phenomenon of business incubation – in this dissertation referred to as incubating activities - is originally intended as a forum that is shielded off from the everydayness of things, with the purpose of adding resources and removing barriers to venture creation. The idea is that entrepreneuring actors will be offered complementary resources and forced to spend time on planning and strategies in a helicopter perspective, which in the end will benefit the process and make venture success more likely. Policy makers together with researchers of entrepreneurship policy and incubation, to a large degree assume that entrepreneurial actors somehow lack skills and resources and cannot easily acquire these themselves, and furthermore that it is possible to affect the resources, behaviour and skills of entrepreneurs. It has nevertheless been shown that enhancing entrepreneurial growth from support activities is not as easy, even if the intentions are good and the resources invested considerable (Blackburn and Schaper 2012, Bruneel et al. 2012, Mason and Brown 2013). It is also taken for granted that entrepreneurs are open to learning and foreign intervention (help and support). This study shows that this is not always the case. Hence, the dissertation explores a highly political and delicate matter touching upon the legitimacy of business incubation.
hdl:10398/9305
Keywords: 650